2018
DOI: 10.32404/rean.v5i3.1892
|View full text |Cite
|
Sign up to set email alerts
|

Divergência Genética Entre Cultivares De Feijão Comum Cultivados No Estado Do Tocantins

Abstract: A escolha e seleção de genitores podem ser auxiliadas por várias análises multivariadas que orientam os melhoristas na tomada de decisão em um programa de melhoramento, dentre elas, podendo destacar as análises de dissimilaridade genética. Diante disso, objetivou-se com este trabalho avaliar a divergência genética de dezenove cultivares de feijão comum cultivado no Estado do Tocantins. O delineamento estatístico adotado foi o de blocos casualizados com quatro repetições. Para identificar a dissimilaridade das … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
4
0
3
Order By: Relevance
“…Among the most used methods to characterize the plant genetic diversity, the multivariate approaches consist in a simultaneous evaluation of a wide range of traits that can make it possible to visualize different characteristics of a data set. These techniques have generated relevant information for studies on plant genetic resources, breeding and conservation since these methods allow, simultaneously, the measurement of different traits (TAVARES et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Among the most used methods to characterize the plant genetic diversity, the multivariate approaches consist in a simultaneous evaluation of a wide range of traits that can make it possible to visualize different characteristics of a data set. These techniques have generated relevant information for studies on plant genetic resources, breeding and conservation since these methods allow, simultaneously, the measurement of different traits (TAVARES et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is suggested that there is genetic diversity of cowpea cultivars used in this study in relation to height in response to potassium fertilization. In a study with genetic divergence between common bean cultivars, there was a group with higher means (p<0.01) composed of five cultivars, where means ranged from 75.8 to 64.4 cm (Tavares et al, 2018). However, Santos et al (2017) in an experiment with three cowpea cultivars did not observed significant differences between the cultivars evaluated for the height variable.…”
Section: Resultsmentioning
confidence: 90%
“…Observou-se que todas as variáveis avaliadas nos 36 genótipos de milho apresentaram diferenças significativas (p≤ 0,05 e p≤ 0,01) (Tabela 2). Estes resultados demonstram que houve, no mínimo, uma cultivar diferindo das demais, sinalizando uma ampla variabilidade fenotípica observada entre híbridos e variedades que permitiram, com precisão, a caracterização de indivíduos superiores [30].…”
Section: Resultados E Discussõesunclassified